A low power biopotential amplifier in 0.35um CMOS for portable EEG signal amplification - Lim, Y.H. (IEEE Computer Society, 2014)
In this paper, a low power differential biopotential amplifier (BPA) targeted for front-end electroencephalogram (EEG) signal amplification is reported. The proposed BPA is chopper stabilized to minimize flicker noise or 1/f noise, improving the fidelity of the signal measurement. This work aims to provide a low power BPA design solution for portable EEG application. This work proposes a non-overlapping clocking scheme for demodulation chopping for chopping artifacts reduction while maintaining low power consumption. This work is simulated in MIMOS 0.35um CMOS process and has achieved around 57dB of gain, ultra-low power consumption of 0.81Î¼W with noise performance of 347nV/sqrt(Hz) and supply voltage of 1.8V. Â© 2014 IEEE.